Micro-credentials in higher education institutions: challenges and opportunities / Nur Hidayah Che Ahmat ... [et al.] - Che Ahmat, Nur Hidayah; Bashir, Muhammad Arif Aizat; Razali, Ahmad Rashidy; Kasolang, Salmiah (Universiti Teknologi MARA, 2021)
The COVID-19 pandemic has changed the education sector locally and globally especially in teaching and learning delivery methods as most universities have adopted online platforms. The present situation is not only challenging but also tests the flexibility of the existing education system. With the help of technology, the existing traditional education system could be more flexible to enable more individuals from around the world to access education. The latest revolution in online education, micro-credential, is growing interest among public and private universities worldwide, including Malaysia. However, to date, little scholarly work is found related to micro-credentials in higher education. This conceptual paper presents an overview of micro-credential and the challenges and opportunities of offering micro-credential certification in the form of digital badges to the national and global market. Recommendations are made to multiple stakeholders (e.g., higher education providers, employers) to enhance the use of certifications for graduate employability. Ideas for further research are also presented.